Upaya Lembaga Pembinaan Khusus Anak dalam Melakukan Bimbingan Islami`: STUDI LPKA KELAS II BANDA ACEH (Jurnal Bimbingan dan Konseling Islam, 2020)
The Class II Banda Aceh Children's Special Guidance Institute (LPKA) has carried out various efforts to provide Islamic guidance to civilian students, including learning to read the Koran, Islamic studies and so on. If seen from the guidance efforts given, there should be a change in attitude and behavior for correctional students in terms of faith, worship, and morals. This study aims to determine first, LPKA's efforts in providing Islamic guidance to students. Second, the method of Islamic guidance that is applied to students. Third, the obstacles that occur in the process of Islamic guidance for students. The method used in this research is descriptive analytical method. Subject taking in this study was carried out using purposive sampling. The results showed that the LPKA had attempted to provide Islamic guidance in the form of learning activities to read the Koran, congregational prayer, zikir. The guidance method applied is by making groups according to the class of students. The obstacles that occur in the guidance process consist of internal factors and external factors. Internal factors such as students' lack of interest. Meanwhile, the external factor is the lack of competent Islamic mentors.